SISTEM PENDUKUNG KEPUTUSAN KARYAWAN BARU PADA PT. LIMA SEMPURNA MAKMUR MENGGUNAKAN METODE FUZZY MAMDANI - Emi Kusumawati (STEKOM PRESS, 2018)
loyee selection based on the application file, calls for interviews and psychological tests and aspects of criteria in employee appraisal that are still done manually and there is no specific application used for the recruitment of new employees and supporting data on the acceptance of new employees has not accurate. The purpose of this study is to create a system to facilitate decision making related to the problem of recruiting new employees using the Fuzzy Mamdani method in order to process data and provide recommendations for decision making in determining employees. 0 Votes · 0 Bookmarks · 0 Requests Selection of employees based on application files, summons for interviews and psychological tests and aspects of criteria in employee appraisal are still done manually and there is no specific application used for the acceptance of new employees and data support in recruiting new employees is not accurate. The purpose of this study is to create a system to facilitate decision making related to the problem of recruiting new employees using the Fuzzy Mamdani method in order to process data and provide recommendations for decision making in determining employees.